2013
DOI: 10.1007/s11606-012-2306-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of VA Women’s Health Fellowships: Developing Leaders in Academic Women’s Health

Abstract: BACKGROUND:The Department of Veterans Affairs (VA) instituted the VA Women's Health Fellowship (VAWHF) Program in 1994, to accommodate the health needs of increasing numbers of female veterans and to develop academic leaders in women's health. Despite the longevity of the program, it has never been formally evaluated. OBJECTIVE: To describe the training environments of VAWHFs and career outcomes of female graduates. DESIGN AND PARTICIPANTS: Cross-sectional webbased surveys of current program directors ( ) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…Mentorship is crucial for women to maintain and hold academic positions. 28 Research on the VA WH graduates have shown that since graduation, nearly half have gone on to hold major leadership positions and that 79% of that population has remained in academics since graduation, compared with 35% of women in academic medicine that do not pursue fellowships, 14 a value that the OWH initially cited as one of the core reasons to develop the National Centers of Excellence in Women's Health. Moreover, many WH fellowships also offer other advanced degrees, such as a dual MBA or MPH that is achievable during fellowship, 9 providing women even more potential as valuable resources for patients, colleagues, future fellows, and society.…”
Section: Value Of Accreditationmentioning
confidence: 99%
“…Mentorship is crucial for women to maintain and hold academic positions. 28 Research on the VA WH graduates have shown that since graduation, nearly half have gone on to hold major leadership positions and that 79% of that population has remained in academics since graduation, compared with 35% of women in academic medicine that do not pursue fellowships, 14 a value that the OWH initially cited as one of the core reasons to develop the National Centers of Excellence in Women's Health. Moreover, many WH fellowships also offer other advanced degrees, such as a dual MBA or MPH that is achievable during fellowship, 9 providing women even more potential as valuable resources for patients, colleagues, future fellows, and society.…”
Section: Value Of Accreditationmentioning
confidence: 99%
“…2 By 2010, 87 physicians had completed a VA AFWH. 3 Recognizing the importance of WH leadership beyond medicine and congruent with its efforts to foster interprofessional training and practice, 4 in 2012, the VA extended training at six recurring and two new sites to nonphysician postdoctoral fellows in clinical fields such as nursing and psychology 5 and developed a National AWHP Coordinating Center. An annual directory of women's health residency and fellowships lists nine 2-year WH fellowships in addition to the eight from VA AFWH, eight 1-year fellowships (two limited to psychiatry), and eight WH residencies.…”
Section: F Oreman and Colleaguesmentioning
confidence: 99%
“…An annual directory of women's health residency and fellowships lists nine 2-year WH fellowships in addition to the eight from VA AFWH, eight 1-year fellowships (two limited to psychiatry), and eight WH residencies. 6 We sought evidence to support Foreman et al's assumptions of benefit as well as evidence for potential harms of pursuing WH fellowship accreditation by reviewing the descriptions of existing WH fellowships and residencies in the Directory of Residency and Fellowship Programs in Women's Health, 6 ACGME requirements for 2-year fellowships 7 , the evaluation of the VA AFWH programs, 3 the case of ACGME accreditation of geriatric fellowships in 1988 leading to a Certificate of Added Qualification, the experience of general internal medicine (GIM) fellowships which remain unaccredited, 8 physician trends away from primary care specialties, [9][10][11] American Boards of Internal Medicine (ABIM) fellowship matching data, 12 and research on gender and status. Table 1 summarizes our assessment of the evidence supporting and opposing accrediting WH fellowships.…”
Section: F Oreman and Colleaguesmentioning
confidence: 99%
See 2 more Smart Citations